Presynaptic release of ATP from superior cervical ganglion of rats modulated by various receptors - Liang Shang-dong; Vizi E Sylvester (Acta Pharmacologica Sinica, 2016)
AIM:To determine whether adenosine 5'-triphosphate (ATP) is released from the superior cervical ganglion (SCG) of rats and whether the release is regulated by presynaptic mechanism. METHODS:Using the luciferin-luciferase technique. RESULTS:Electric stimulation evoked the release of ATP from the rat SCG. Adenosine (100 mumol.L-1), P1(A1) purinoceptor agonist N6-cyclopentyladenosine (0.1 mumol.L-1), the muscarinic agonist oxotremorine (1 mumol.L-1), and 5-hydroxytryptamine (100 mumol.L-1) decreased the evoked release of ATP from the rat SCG. On the contrary, P1(A1) purinoceptor antagonist 8-cyclopentyl-1,3-dipropylxanthine (10 nmol.L-1), P2 purinoceptor antagonist pyridoxal-5-phosphate-6-azophenyl-2',4-disulphonic acid (10 mumol.L-1), muscarinic antagonist atropine (1 mumol.L-1), alpha 2 adrenoceptor antagonist yohimbine (3 mumol.L-1), D2 dopamine receptor antagonist sulpiride (20 mumol.L-1), and histamine (100 mumol.L-1) increased the evoked release of ATP from the rat SCG. CONCLUSION:ATP is released from the rat SCG and the release of ATP can be presynaptically modulated by P1(A1), P2, muscarinic, alpha adrenergic, D2, 5-HT, and H1 receptor agonists and antagonists.